Iowa RBA, March 11-24, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for March 11-24, 1996. Highlights of the update include sightings of a female White-winged Scoter, a first year Glaucous Gull, Thayer's Gulls and a female White-winged Crossbill. Epson - sheet feed/flatbed